THE DIVERSITY OF LEPIDOPTERA (INSECTA) IN MOUNT KENDENG AND MOUNT BOTOL, GUNUNG HALIMUN NATIONAL PARK, WEST JAVA - Atmowidi, Tri; Prawasti, Taruni Sri; Sugiri, Nawangsari; Kurniawan, Yana (BERITA BIOLOGI, 2001)
-